PROBLEMATIK PENATAAN JENIS DAN HIERARKI PERATURAN PERUNDANG-UNDANGAN - Efendi, A'an (Faculty of Law, Parahyangan Catholic University, 2019)
Indonesia over a period of numerous years has had four different regulations with the same intent, i.e. to reorder the hierarchy of the various forms and types of legislative products. This effort apparently has not yet been a success. In this article, the author shall attempt to identify the core problem hindering the effort at re-ordering and discuss how other countries, notably, Germany, France, and the Netherland tackle the same comparable problem. The approach used here is doctrinal or dogmatic, and in addition a comparative law method. One important recommendation resulting from this study is that it would be better if the Indonesian legislator re-order the hierarchy of the various forms and types of legislation on the basis of the hierarchal order of the organ issues the legislative product.